A disciplina eletiva dos barracos às mansões: relações com os saberes - Vieira, Andréa Antunes Lemo (Universidade Federal de São Carlos, 2015)
This research aims to analyze the relationship with regard to the knowledge that can be established by students of Basic Education while they are studying the elective course, of interdisciplinary nature: “From shacks to mansions.” In this discipline, the student has the opportunity to explain both the knowledge as the types of relationships established with diverse knowledge, including the extracurricular and school. The instruments used for the construction of the data were: 1- observation of classes developed in the context of elective 2 - records in the logbook of the researcher, 3 - semi-structured interviews with teachers who teach the discipline and students of basic education who attended the subject and 4 – questionnaires applied to students who participated in the discipline. The question that led the research was: “What relationships with knowledge are explained by the students of basic education whilst undertaking the Elective Course, entitled” “From Shacks to Mansions?”. In answering the question I considered the studies of Charlot (2000, 2001, 2005), with regard to the concept of knowing, as well as the research of Kanbach (2005), Barros (2010) and Pompey (2011) which deal with the subject. As a result, it can be said that the knowledge explained by learners does not necessarily address just the school contents. They prioritize and are related to the feelings and opinions that students have about: 1) what they will do in the discipline, 2) the construction of models, 3) interest in the profession, 4) the teaching used by teachers, 5) the treatment given to them by the teachers.
Keywords: Saberes; Disciplina eletiva; Interdisciplinaridade; Knowledge; Elective course; Interdisciplinary; CIENCIAS HUMANAS::EDUCACAO